Prediction of sound absorption coefficient for double layer rubberised concrete blocks - Haron, Zaiton; Jusli, Euniza; Md Nor, Hasanan; Putra Jaya, Ramadhansyah; Yaacob, Haryati; Yahya, Khairulzan; Mohamad, Azman; Yahya, Musli Nizam (Science Publisher Corporation, 2018)
Nowadays rubberised concrete is used to support construction sustainability and contribute to a better development of efficient construction material, in particular by using waste rubber tyre. The use of rubber in block pavement is one of the actions in order to reduce the noise from tyre-road interaction and hence able to reduce pass by noise pollution. In this paper, the influence of waste rubber tyre as the replacement for aggregate on the sound absorption coefficient of double layer rubberised concrete blocks was investigated. Non acoustics and acoustics experimental investigations were carried out on a series of block with thickness of 80 mm with facing layer (FL) of block varies in thickness from 10 to 40 mm. FL and bottom layer consist of concrete mixture containing waste tyre rubber granules (RG) of 5 mm to 8 mm and 1 mm to 4 mm, respectively as replacement of natural aggregate within the range of 10-40%. The ratio for cement: aggregate: sand was 1: 1.7:1.5 and water to cement (w/c) ratio of 0.47. Noun acoustics parameters include density, compressive strength, water absorption and porosity. Acoustic parameters investigation of specimens of double layer block showed that concrete pavement blocks have maximum sound absorption located at low frequency of 500 to 700 Hz. This indicates that it is suitable for application of mitigation of low speed traffic condition. A model was developed to predict the maximum sound absorption coefficient of the double layer block pavements which included the percentage of rubber content, thickness of FL and porosity as statistically significant predictor (p < 0.05). This would benefit the road engineers in managing traffic noise management as the sound absorption coefficient is the key important element in reducing tyre/road interaction noise.